A solvent- and vacuum-free route to large-area perovskite films for efficient solar modules - Chen, Han; Ye, Fei; Tang, Wentao; He, Jinjin; Yin, Maoshu; Wang, Yanbo; Xie, Fengxian; Bi, Enbing; Yang, Xudong; Grätzel, Michael; Han, Liyuan (Nature (London), 2017)
A new deposition method for solar-panel polycrystalline perovskite thin films enables the production of large-area uniform films and avoids the need for common solvents or vacuum. Expanding efficient solar devices Hybrid inorganic–organic perovskites are the most likely materials to replace silicon as absorber layers for solar cells, but issues with stability and scaling-up thin films mean that large-scale production is not yet possible. Liyuan Han and colleagues have developed a new deposition method for polycrystalline thin films that does not rely on spin- or drip-coating precursors in solvent or on vacuum deposition, and is therefore more amenable to larger-area films than are previous techniques. The procedure uses gaseous precursors and application of pressure, and has enabled a device with an area of 36 square centimetres to be certified at 12.1 per cent power conversion efficiency. Recent advances in the use of organic–inorganic hybrid perovskites for optoelectronics have been rapid, with reported power conversion efficiencies of up to 22 per cent for perovskite solar cells 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 . Improvements in stability have also enabled testing over a timescale of thousands of hours 10 , 11 , 12 , 13 , 14 . However, large-scale deployment of such cells will also require the ability to produce large-area, uniformly high-quality perovskite films. A key challenge is to overcome the substantial reduction in power conversion efficiency when a small device is scaled up: a reduction from over 20 per cent to about 10 per cent is found 15 , 16 , 17 , 18 , 19 , 20 , 21 when a common aperture area of about 0.1 square centimetres is increased to more than 25 square centimetres. Here we report a new deposition route for methyl ammonium lead halide perovskite films that does not rely on use of a common solvent 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 or vacuum 3 : rather, it relies on the rapid conversion of amine complex precursors to perovskite films, followed by a pressure application step. The deposited perovskite films were free of pin-holes and highly uniform. Importantly, the new deposition approach can be performed in air at low temperatures, facilitating fabrication of large-area perovskite devices. We reached a certified power conversion efficiency of 12.1 per cent with an aperture area of 36.1 square centimetres for a mesoporous TiO 2 -based perovskite solar module architecture.